Multicompartment metabolism in papillary thyroid cancer. (15th December 2015) - Curry, Joseph M.; Tassone, Patrick; Cotzia, Paolo; Sprandio, John; Luginbuhl, Adam; Cognetti, David M.; Mollaee, Mehri; Domingo‐Vidal, Marina; Pribitkin, Edmund A.; Keane, William M.; Zhan, Tingting; Birbe, Ruth; et al.
Abstract : Objectives/Hypothesis: In many cancers, varying regions within the tumor are often phenotypically heterogeneous, including their metabolic phenotype. Further, tumor regions can be metabolically compartmentalized, with metabolites transferred between compartments. When present, this metabolic coupling can promote aggressive behavior. Tumor metabolism in papillary thyroid cancer (PTC) is poorly characterized. Study Design: Immunohistochemical staining of tissue samples. Methods: Papillary thyroid cancer specimens from 46 patients with (n = 19) and without advanced disease (n = 27) were compared to noncancerous thyroid tissue (NCT) and benign thyroid specimens (n = 6 follicular adenoma [FA] and n = 5 nodular goiter [NG]). Advanced disease was defined as the presence of lateral neck lymphadenopathy. Immunohistochemistry was performed for translocase of outer mitochondrial membrane 20 (TOMM20), a marker of oxidative phosphorylation, and monocarboxylate transporter 4 (MCT4), a marker of glycolysis. Results: Papillary thyroid cancer and FA thyrocytes had high staining for TOMM20 compared to NCT and nodular goiter (NG) ( P < 0.01). High MCT4 staining in fibroblasts was more common in PTC with advanced disease than in any other tissue type studied ( P < 0.01). High MCT4 staining was found in all 19 cases of PTC with advanced disease, in 11 of 19 samples with low‐stage disease, in one of five samples of FA, in one of 34 NCT, and in 0 of six NG samples. Low fibroblast MCT4 staining in PTC correlated with the absence of clinical adenopathy ( P = 0.028); the absence of extrathyroidal extension ( P = 0.004); low American Thyroid Association risk ( P = 0.001); low AGES (age, grade, extent, size) score ( P = 0.004); and low age, metastasis, extent of disease, size risk ( P = 0.002). Conclusion: This study suggests that multiple metabolic compartments exist in PTC, and low fibroblast MCT4 may be a biomarker of indolent disease. Level of Evidence: N/A. Laryngoscope, 126:2410–2418, 2016